Qatar Healthcare Workers' COVID-19 Vaccine Hesitancy and Attitudes: A National Cross-Sectional Survey - Kumar, Rajeev; Alabdulla, Majid; Elhassan, Nahid M.; Reagu, Shuja Mohd (Frontiers in Public Health, 2021)
Introduction: Healthcare workers are the critical frontline workforce of the COVD-19 pandemic and are considered a target group for vaccination. Hesitancy to vaccinate is a major concern that can jeopardize the vaccination programme. The hesitancy rates in the general population and healthcare workers (HCWs) vary globally, and more importantly, hesitancy in HCWs is of particular concern, as it can influence the wider population. Materials and Methods: The present study evaluated the vaccine hesitancy rate and its sociodemographic and attitudinal factors among the HCWs in the state of Qatar. We conducted a national cross-sectional survey using a validated hesitancy measurement tool between October 15 and November 15, 2020. A total of 7,821 adults above the age of 18 years out of the 2.3 million adult Qatari residents completed the survey. While majority of the participants were from the general public, 1,546 participants were HCWs. Sociodemographic data, along with attitudes and beliefs around COVID-19 vaccination, were collected from the respondents. Results: We found that 12.9% of the study participants showed vaccine hesitancy, defined as definitely or probably will not take the vaccine if offered, and 25.31% reported that they were unsure about the uptake of the COVID-19 vaccine. Female respondents were more hesitant toward the vaccine. Safety and efficacy concerns of vaccine were the significant predictors of vaccine hesitancy. The primary predictor for vaccine acceptance was a better understanding of the disease and vaccine. Discussion: Overall, 1 in 8 HCWs were reluctant to get vaccinated against COVID-19, mainly due to concerns about the vaccine's efficacy and safety. Education about the vaccine's safety and efficacy can potentially improve acceptance among healthcare workers.